Health-related quality of life after prosthodontic rehabilitation in patients with COVID-19-associated mucormycosis: A systematic review - Gunjan Chouksey; Rupali Choure; Kritika Singhal (The Journal of Indian Prosthodontic Society)
Health-related quality of life (HRQOL) measures an individual’s ability to function optimally in various aspects of life and their subjective sense of well-being across the physical, mental, and social dimensions of health. COVID-19-associated mucormycosis often necessitates aggressive surgical removal of infected tissues and restoration of the defect. Evaluating patient satisfaction and HRQOL following prosthodontic rehabilitation is essential for assessing the effectiveness of interventions on individuals dealing with their condition. This systematic review aimed to evaluate the impact of prosthodontic rehabilitation on the HRQOL of individuals affected by COVID-19-associated mucormycosis. The research strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was registered with the International Prospective Register of Systematic Reviews (PROSPERO 2023CRD42023495778). Comprehensive searches across databases such as PubMed, Cochrane Library, Google Scholar, and Semantic Scholar were done to include studies after the year 2020, written in English language, regardless of geographic location, which presented data on prosthodontic interventions for individuals affected by COVID-19-associated mucormycosis. Independently, the three authors conducted a comprehensive quality assessment of the selected studies using the National Heart Lung and Blood Institute (NHLBI) study quality assessment tool to gauge the risk of bias specifically for before–after (pre–post) studies lacking a control group. A total of 116 records were screened, out of which 109 records were excluded. Eight studies were included in the study. HRQOL assessment after prosthodontic intervention included functional, physical, social, and psychological limitations. Questionnaires that were included in the studies were the Obturator Functioning Scale, Appearance Anxiety Inventory, Patient Health Questionnaire, auditory perception analysis, Oral Health Impact Profile, and the Liverpool Oral Rehabilitation Questionnaire. The HRQOL was reported compositely in 2 out of 8 studies. There was an improvement after prosthodontic rehabilitation in all the studies. HRQOL in patients with COVID-19-associated mucormycosis shows improvement after prosthodontic rehabilitation. Obturators and zygomatic implant-supported prostheses are preferred options for rehabilitation in patients who have undergone maxillectomy due to COVID-19-associated mucormycosis. Prosthodontic rehabilitation has a positive impact on the HRQOL of individuals affected by COVID-19-associated mucormycosis improving their functional, physical, social, and psychological well-being.